O avanço do dendê no nordeste paraense, seus impactos a produção familiar e a projeção para o município de Santo Antônio do Tauá - SIQUEIRA, Alex dos Santos (2019)
This article aims to evaluate the way the state, through public policies, has been acting in the rural environment of Pará from the implementation of the Program of Sustainable Production of palm oil in Brazil, 2010. The social and environmental impacts that the cultivation of oil palm (Elaeis guineensis) destined for the extraction of palm oil and palm kernel oil has been causing family production since the incorporation of families into production. The information was collected from the IBGE and FAPESPA database, by bibliographic review and secondary data, since it was not possible to contact family producers linked to Dendetaua and the Rural Producers' Union of Santa Izabel do Pará and Santo Antônio do Tauá. As a result it was noticed a subordination of rural producers to companies showing a relationship of power and a lack of social and economic rise, leading to believe that the activity is not inclusive and sustainable able to contribute significantly to the development promotion as objective the government project.